Third-line antiretroviral therapy in low-income and middle-income countries (ACTG A5288): a prospective strategy study. Issue 9 (September 2019) - Grinsztejn, Beatriz; Hughes, Michael D; Ritz, Justin; Salata, Robert; Mugyenyi, Peter; Hogg, Evelyn; Wieclaw, Linda; Gross, Robert; Godfrey, Catherine; Cardoso, Sandra W; Bukuru, Aggrey; Makanga, Mumbi; et al.
Summary: Background: Antiretroviral therapy (ART) management is challenging for individuals in resource-limited settings presenting for third-line treatment because of complex resistance patterns, partly due to reduced access to viral load monitoring. We aimed to evaluate use of newer antiretroviral drugs and contemporary management approaches, including population-based sequencing, to select appropriate antiretrovirals, plasma viral load monitoring, and interventions to improve adherence in individuals presenting with second-line viral failure. Methods: A5288 was a phase 4, third-line ART strategy study done at 19 urban sites in ten countries that enrolled adult participants with confirmed plasma HIV-1 RNA (viral load) of 1000 copies per mL or more after more than 24 weeks of protease inhibitor-based second-line ART. The primary objective was to use antiretrovirals (raltegravir, etravirine, and ritonavir-boosted darunavir) and diagnostic monitoring technologies, including viral load, genotyping, and adherence support to achieve viral load suppression (defined as ≤200 copies per mL) in 65% or more of participants. ART history and real-time drug resistance genotypes were used to assign participants to one of four cohorts: cohort A (no lopinavir resistance) stayed on second-line ART and cohorts B (B1, best available nucleoside reverse transcriptase inhibitors [NRTIs] plus ritonavir-boosted darunavir plus raltegravir; B2, ritonavir-boosted darunavir plus raltegravir plus etravirine; B3, ritonavir-boosted darunavir, raltegravir, and either tenofovir plus emtricitabine or tenofovir plus lamivudine), C (ritonavir-boosted darunavir plus raltegravir plus tenofovir-emtricitabine or tenofovir plus lamivudine), and D (best available NRTIs plus ritonavir-boosted darunavir plus raltegravir) were defined by increasing levels of resistance and received appropriate regimens, including new antiretrovirals. Participants in Cohort B without detectable hepatitis B surface antigen were assigned by blocked randomisation to cohorts B1 and B2, and those with detectable hepatitis B surface antigen were assigned to cohort B3. The trial is registered withClinicalTrials.gov, numberNCT01641367 . Findings: From Jan 10, 2013, to Sept 10, 2015, 545 participants were enrolled. 287 (53%) were assigned to cohort A, 74 (14%) to B1, 72 (13%) to B2, eight (1%) to B3, 70 (13%) to C, and 34 (6%) to D. Overall, 349 (64%, 95% CI 60–68) participants achieved viral suppression at week 48, with proportions varying from 125 (44%) of 287 in cohort A to 65 (88%) of 74 in cohort B1, 63 (88%) of 72 in B2, eight (100%) of eight in B3, 63 (90%) of 70 in C, and 25 (74%) of 34 in D. Participants in cohort A remained on their second-line protease inhibitor, and had the most participants with grade 3 or higher adverse events (147 [51%]). Interpretation: Targeted real-time genotyping to select third-line ART can appropriately allocate more costly antiretrovirals to those with greater levels of HIV drug resistance. Funding: National Institutes of Health.